Pengaruh Modal Psikologi Dan Keterlibatan Pegawai Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Mediasi (Studi Pegawai Politeknik Ilmu Pelayaran Semarang) - Adhi Prastistha Silen (Universitas Airlangga, 2016)
The research objective to be achieved to analyze the effect of psychological capital and employee involvement to job satisfaction in Seamanship Polytechnic Semarang. To analyze the effect of psychological capital, employee engagement and job satisfaction to employee performance in Seamanship Polytechnic Semarang. To analyze the effect of psychological capital and employee involvement to employee performance, moderated by Job Satisfaction in Seamanship Polytechnic Semarang In this study took the population in this study were employees of the Polytechnic Semarang Seamanship, amounting to 218 persons. Sampling with random sampling technique that randomly sampling 142 respondents. Based analyst who conducted the study concluded that psychological capital and employee involvement and significant positive effect on job satisfaction. Capital psychology, employee engagement and job satisfaction positive and significant impact on performance. Job satisfaction does not mediate the effect of psychological capital and employee involvement to employee performance.